Perioperative NT-proBNP in Lung Cancer Surgery: A Narrative Review of Mechanisms, Predictive Value, and Clinical Implications - Mădălina Butaș; Sonia Elena Popovici; Stelian Adrian Ritiu; Gabriel Veniamin Cozma; Vasile Gaborean; Iulia Najette Crintea; Maria Sala-Cirtog; Alina Ramona Buzatu; Roxana Buzas; Marilena Dinuți (Journal of Clinical Medicine, 2026)
Background: NT-proBNP is a mechanistically grounded biomarker of ventricular wall stress with established prognostic value in cardiac surgery, but its perioperative role in lung cancer resection remains incompletely characterised. Pulmonary resection imposes unique haemodynamic stressors—including one-lung ventilation-induced right ventricular afterload increase, permanent pulmonary vascular bed reduction, and ischaemia–reperfusion injury—that create a distinct biological context for natriuretic peptide elevation not represented in general surgical cohorts. Methods: A narrative review of the literature was conducted through systematic searches of PubMed, EMBASE/MEDLINE, and the Cochrane Library (January 2000–June 2026), supplemented by manual reference screening. Approximately 135 articles were included in the final synthesis. Results: Perioperative NT-proBNP elevation predicts postoperative atrial fibrillation, major adverse cardiovascular events, and long-term survival after lung resection, with effect sizes substantially exceeding those reported in general surgical populations. The PRESAGE trial established that NT-proBNP-guided prophylaxis reduces postoperative atrial fibrillation from 40% to 6% in high-risk patients. No thoracic surgery-specific NT-proBNP threshold has been prospectively validated in a multicentre setting, and approximately half the evidence base derives from BNP rather than NT-proBNP assays, precluding direct threshold synthesis. Surgical approach—particularly robot-assisted thoracoscopy—modulates postoperative biomarker elevation through OLV duration rather than inflammatory burden alone. The combination of NT-proBNP with high-sensitivity troponin identifies a dual-elevation subgroup with a MACE rate of 18.4%. Conclusions: NT-proBNP measurement is clinically actionable in thoracic surgery but requires assay-standardised, multicentre validation of population-specific thresholds stratified by resection extent and surgical approach. A dual biomarker strategy combining NT-proBNP with high-sensitivity troponin represents the most evidence-based perioperative risk stratification framework currently available.